A black Phosphorus/BiVO4(010) heterostructure for promising photocatalytic performance: First-principles study. (August 2020) - Zhang, Rui; Hao, Guoqiang; Li, Hongbo; Ye, Xiaojun; Gao, Shangpeng; Yuan, Xiao; Liu, Cui
Abstract: Black phosphorus-based two-dimensional heterostructure photocatalysts have attracted much attention due to their prominent photocatalytic performance. However, theoretical analysis on the mechanism of photocatalytic activity is still lacking. Firstly, we comprehensively analyzed the structural and electronic properties of BP/BiVO4 (010) heterostructure. It is found that the BP/BiVO4 (010) composite was a stable interface and formed a type-II heterostructure. The density of states, Bader charge, and charge density difference were elucidated and the results show that the BiVO4 (010) slab can act as a protect and supporting layer to protect monolayer BP from oxidation and deformation while still maintaining its electronic properties. In addition, the BP/BiVO4 (010) is forming a built-in electric field from BP to BiVO4, which facilitate the separation of e−/h + pair at the BP/BiVO4 interface and enable the water with a high redox potential. These results provide monolayer BP-based composite photocatalysts and insightful understanding of the physical mechanism of this new synthesized system. Highlights: A type-II BP/BiVO4 (010) heterostructure for promising photocatalytic performance is proposed. The interfacial vdW interactions and electronic properties of BP/BiVO4 (010) heterostructure are performed. BiVO4 can be a promising candidate either as a capping or supporting layer for encapsulating BP layer.